Controlling the crystallisation of oxide materials by solvothermal chemistry: tuning composition, substitution and morphology of functional solids. Issue 40 (25th August 2016) - Hiley, Craig I.; Walton, Richard I.
Abstract : Three aspects in the synthesis of oxides under solvothermal conditions are reviewed: materials discovery, substitutional chemistry and crystal habit control. Abstract : We provide an overview of currently emerging areas in the solvothermal synthesis of polycrystalline oxide materials that illustrate how tailoring synthesis may be possible to target the formation of functional solids. We illustrate various levels of control in preparation of functional oxides with interesting structures and compositions by choosing examples of three aspects of recent chemistry: (1) materials discovery, (2) substitutional chemistry and (3) adjustment of crystal morphology and size. This includes new oxides of ruthenium, iridium and of bismuth, novel substitutional chemistry of CeO2 and TiO2, and control of crystal form of binary and ternary oxides. The accumulated research illustrates the potential for fine control of the properties of materials by targeted crystallisation of solid oxides with selected chemical composition and particle shape and dimensions from the nanoscale to the micronscale. These benefits uniquely arise from chemical variation possible by use of solution-mediated crystallisation. We conclude by discussing how future work must focus on developing predictive synthesis, where synthesis conditions could be selected to design a solid material with desired properties.